On garden style - Williams, Bunny (Simon & Schuster, 1998)
First published in 1998, On Garden Style established Bunny Williams as a reputable expert on gardens. In Bunny Williams on Garden Style, Williams visits impeccably designed gardens around the world, shedding light on the key components that make a garden so appealing and idyllic. For Williams, gardens offer an escape, and she imparts vital information on how to envision your garden and design a space that translates into a lush sanctuary reflecting your taste and style. Once you've imagined your garden, Williams offers advice for bringing it to fruition-the garden structure," furnishing the space, and establishing an aesthetic. The book also includes plant lists, a reading list, and more. Filled with new photography of spectacular gardens, this latest volume is both a wonderful inspiration and a practical guide to gardening from one of the world's most renowned design experts.